2019
DOI: 10.1002/jmv.25401
|View full text |Cite
|
Sign up to set email alerts
|

Functional and clinical consequences of changes to natural killer cell phenotypes driven by chronic cytomegalovirus infections

Abstract: Cytomegalovirus (CMV) infections may affect natural killer (NK) cells and are implicated in age‐related disorders—notably poor vascular endothelial function. Changes may be greater in renal transplant recipients (RTR) as they have a high burden of CMV and may influence antibody‐dependent cellular cytotoxicity (ADCC) responses to viral antigen. We obtained blood mononuclear cells from RTR stable after transplantation (n = 27) and age‐ and sex‐matched controls (n = 28). Natural killer (NK) cells were assessed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Neither IgA, IgG and IgM antibodies reactive with HCMV antigens nor HCMV vIL-10 were detectable in saliva or plasma (Table 1; data not shown). Analysis of her PBMC by flow cytometry revealed expanded populations of FcγRand NKG2C + NK-cells, characteristic of HCMV infection [17,18] (Table 1). The FcγRpopulation comprised 27.3% of CD3 -CD56 dim NK-cells, compared with a median (range) of 9.1 (5.4-19.1)% for other seronegative healthy controls (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither IgA, IgG and IgM antibodies reactive with HCMV antigens nor HCMV vIL-10 were detectable in saliva or plasma (Table 1; data not shown). Analysis of her PBMC by flow cytometry revealed expanded populations of FcγRand NKG2C + NK-cells, characteristic of HCMV infection [17,18] (Table 1). The FcγRpopulation comprised 27.3% of CD3 -CD56 dim NK-cells, compared with a median (range) of 9.1 (5.4-19.1)% for other seronegative healthy controls (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Results were presented as arbitrary units (AU)/mL based on a standard plasma pool [13,14]. FcRγand NKG2C + NK cells (CD3 -CD56 dim ) and Vδ2-γδ T-cells were enumerated using multicolor flow cytometry, as the populations are expanded in CMV-seropositive RTR [18,19]. Enzyme linked immunosorbent spot (ELISpot) assays utilized anti-IFN antibodies (MabTech, Stockholm, Sweden).…”
Section: Immunological Responses To Hcmvmentioning
confidence: 99%
“…It has been reported that the gB genotypes vary in their ability to stimulate cell-mediated or cytotoxic immune response. 10 , 11 Therefore, variations in gB are likely to have significant effects on the pathogenesis of CMV disease and the spectrum of host cells infected by the virus. Our previous studies also confirmed that the gB1 genotype had more virulence in infants with symptomatic CMV disease.…”
Section: Discussionmentioning
confidence: 99%
“…Results were presented as arbitrary units (AU)/mL based on a standard plasma pool [14]. FcRγ − and NKG2C + NK cells (CD3 − CD56 dim ) and Vδ2 − γδ T-cells were enumerated using multicolour flow cytometry, as the populations are expanded in CMV-seropositive RTR [18,19]. Gating strategies are illustrated in Figure 1 and Supplementary Materials Figure S1.…”
Section: Immunological Responses To Hcmvmentioning
confidence: 99%